2017
DOI: 10.1007/s11418-017-1107-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of anti-inflammatory constituents in Phellodendri Cortex and Coptidis Rhizoma by monitoring the suppression of nitric oxide production

Abstract: Phellodendri Cortex (Obaku in Japanese) and Coptidis Rhizoma (Oren), both of which contain berberine, have been used to prepare the kampo formula orengedokuto to treat inflammatory diseases, including dermatitis, gastric ulcers, and gastritis. These drugs are blended differently in other formulas, such as the use of Phellodendri Cortex in shichimotsukokato to treat hypertension and Coptidis Rhizoma in hangeshashinto to treat diarrhea and stomatitis. However, the differences in their medicinal properties are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 29 publications
3
36
0
Order By: Relevance
“…Coptis Rhizome is one of the components of a formula, Orengedokuto, which has been used to treat in ammatory disease [43], and berberine is strongly suggested to be responsible for its anti-in ammatory effect [44,45]. In our study, we have con rmed the in vivo anti-malarial activity of Coptis Rhizome, but the Orengedokuto, whose 33.3% content [36] is Coptis Rhizome did not show a comparable effect on the reduction of parasitemia.…”
Section: Discussionmentioning
confidence: 51%
“…Coptis Rhizome is one of the components of a formula, Orengedokuto, which has been used to treat in ammatory disease [43], and berberine is strongly suggested to be responsible for its anti-in ammatory effect [44,45]. In our study, we have con rmed the in vivo anti-malarial activity of Coptis Rhizome, but the Orengedokuto, whose 33.3% content [36] is Coptis Rhizome did not show a comparable effect on the reduction of parasitemia.…”
Section: Discussionmentioning
confidence: 51%
“…Specific pathogen‐free, male Wistar rats (Charles River Laboratories Japan Inc., Yokohama, Japan) were housed at 21–23°C under a 12‐hr light–dark cycle with a γ‐ray‐irradiated CRF‐1 diet (Charles River Laboratories Japan Inc.) and water available ad libitum and acclimated for at least a week. Hepatocytes were prepared from the liver of rats (6‐ to 8‐week‐old, 250–300 g of body weight), according to the previously published method (Fujii et al, ; Kanemaki, Kitade, Hiramatsu, Kamiyama, & Okumura, ). Briefly, the anesthetic combination of medetomidine hydrochloride (0.40 mg/kg body weight; Nippon Zenyaku Kogyo Co., Ltd., Koriyama, Fukushima, Japan), midazolam (2.0 mg/kg body weight; Astellas Pharma Inc., Tokyo, Japan), and butorphanol tartrate (3.5 mg/kg body weight; Meiji Seika Pharma Co. Ltd., Tokyo, Japan) was administered intraperitoneally to a rat, and the liver was perfused with collagenase (FUJIFILM Wako Pure Chemical Corporation, Osaka, Japan) from the portal vein.…”
Section: Methodsmentioning
confidence: 99%
“…Specific pathogen‐free, male 7‐week‐old Lep ob/ob ( ob/ob ) and Lep +/+ (wild‐type) mice (Japan SLC, Inc., Hamamatsu, Japan) were housed at 21–23°C under a 12‐hr light–dark cycle with a γ‐ray‐irradiated CRF‐1 diet and water available ad libitum and acclimated for 1 week. Then each type of the mice (eight mice per type) was randomly assigned into two groups (four mice per group) on Day 0 and fed a γ‐ray‐irradiated CRF‐1 diet with/without 1% EtOAc‐soluble fraction for 7 days with water available ad libitum, according to the previously published method to administer a fraction of herbal medicine to mice (Fujii et al, ). Blood was drawn by a small incision in the tail to measure glucose levels using a Glucocard® PlusCare GT‐1820 Monitoring System (Arkray, Inc., Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Limonin, one of the compounds found in ER [13,14], is the major limonoid and a bitter compound, mainly found in seeds. Several studies have indicated that limonin shows biological activities, including antioxidant, antiinflammatory, and antiviral effects [15][16][17]. Validation studies have demonstrated the anticancer effects of limonin in various cancer cell lines [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%